Транспозиция темпорально-субъектных и количественно-субъектных предложений (на материале литовского и английского языков) - Валейка, Л. (Kalbotyra, 1979)
By a temporal subjective sentence is meant a predicative construction with an obligatory temporal complement of the verb (e. g. Paskaita tęsėsi valandą: The lecture lasted an hour); by a quantitative subjective sentence is meant a predicative structure with an obligatory quantitative complement (Mašina sveria toną: The lorry weighs a ton).In Lithuanian the former sentence yields nominal word-combinations representing nominalizations of two components, nominal and word-combinations representing nominalizations of the sentence as a whole; in English, only two-constituent nominal word-combinations are obtained. The notable fact about the adjunct expressed by a noun denoting a stretch of time is that it cannot be transformed into the corresponding adjective: the morphological change involves a semantic change (dienos darbas* ← +dieninis darbas). Nominal word-combinations derived from the latter sentence are more variegated from a structural point of view. The constituent denoting a unit of measurement usually precedes the constituent denoting the object subjected to measurement. This is true of both Lithuanian and English (sliklinė vandens: a glass of water). Word-combinations in which the quantitative noun follows the material noun are not synonymous with the former: they differ in meaning (vandens stiklinė – a water glass), the difference being especially obvious in English.